1986
DOI: 10.1128/mcb.6.12.4379
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic transformation of rat 3Y1 cells by a transcriptionally activated human c-myc gene and stabilization of p53 cellular tumor antigen in the transformed cells.

Abstract: Transformed foci were obtained in rat 3Y1 fibroblasts cotransfected wtih pRmyc 27 (transcriptionally activated c-myc) and pSV2neo DNA. RmycY cell lines (1 to 7) were established from these foci. RmycY cells were small and round and contained enlarged nucleoli in the nucleus. The myc gene was expressed in these cell lines at a much higher level than in 3Y1 cells and at a level similar to that in HL-60 cells. These cell lines formed colonies in soft-agar culture and tumors in syngeneic rats transplanted with Rmy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…This identifies p53 as a target, direct or indirect, of myc in this system. This result is consistent with previous observations that p53 is among the proteins that are overexpressed in cells whose growth characteristics have been altered by chronic c-myc overexpression (Shiroki et al, 1986), although it has been difficult in such systems to discriminate obligate responses to myc from long term indirect effects. As discussed later, other independent molecular data argue that p53 is a good candidate for direct regulation by myc.…”
Section: Regulatory Capacity Of Conditional Myc Expressionsupporting
confidence: 93%
“…This identifies p53 as a target, direct or indirect, of myc in this system. This result is consistent with previous observations that p53 is among the proteins that are overexpressed in cells whose growth characteristics have been altered by chronic c-myc overexpression (Shiroki et al, 1986), although it has been difficult in such systems to discriminate obligate responses to myc from long term indirect effects. As discussed later, other independent molecular data argue that p53 is a good candidate for direct regulation by myc.…”
Section: Regulatory Capacity Of Conditional Myc Expressionsupporting
confidence: 93%
“…Since increased levels of mutated p53 protein may be necessary for inactivation of wild-type p53 protein (29)(30)(31), the biological consequences of different mutations may vary. Even among mutations leading to accumulation of p53 protein, there is variable malignant potential (2,7,28).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have comparatively analyzed the N-linked sugar-chain structures of cell-membrane giycoproteins ob-tained from rat 3Yl cells and their c-myc-transfected cells which express the c-myc gene at a 20 to 40 times higher level than control 3Y 1 cells and exhibit high tumorigenicity when injected into syngeneic newborn rats (Shiroki et al, 1986). The results indicated that tri-and tetra-antennary oligosaccharides having the GlcNAcP 1-+6 branching and/or the GlcNAcP 1+4 branching increase with the decrease of biantennary oligosaccharides in the transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…RmycY 1 cells thus established as a transformed cell line expressed the c-myc gene at a much higher level than 3Y 1 cells and formed colonies in soft-agar culture and tumors in syngeneic rats (Shiroki et al, 1986). Cells were cultured as described previously (Shiroki et al, 1986) and harvested at logarithmic phase by scraping into phosphate-buffered saline, PH 7.4. The harvested cells were disrupted in hypotonic solution and subjected to the centrifugation procedure to obtain the membrane preparation as described previously .…”
Section: Cells and Preparation Of Cell Membrane Glycoproteinsmentioning
confidence: 99%